2018
DOI: 10.1098/rsif.2018.0270
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the windlass mechanism on arch-spring mechanics during dynamic foot arch deformation

Abstract: The function of the human foot is described dichotomously as a compliant structure during mid-stance and a stiff lever during push-off. The arch-spring and the windlass mechanisms, respectively, describe each of these behaviours; however, their interaction has not been quantified to date. We hypothesized that by engaging the windlass mechanism with metatarsophalangeal joint (MTPJ) dorsiflexion, we would observe stiffening of the arch and reduced energy absorption and dissipation during dynamic compressions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
92
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 27 publications
(64 reference statements)
7
92
2
1
Order By: Relevance
“…However, the small increases in MTP joint dorsiflexion angles caused by toe springs in this study did not affect measured arch stiffness. This result corresponds to the findings of Welte et al 14 , who used static loading to compress the arches of sitting participants at different toe dorsiflexion angles, and found that engaging the windlass mechanism did not increase arch stiffness. A possible explanation might be the flexibility of the plantar aponeurosis, which stretches as the arch is loaded 44 46 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the small increases in MTP joint dorsiflexion angles caused by toe springs in this study did not affect measured arch stiffness. This result corresponds to the findings of Welte et al 14 , who used static loading to compress the arches of sitting participants at different toe dorsiflexion angles, and found that engaging the windlass mechanism did not increase arch stiffness. A possible explanation might be the flexibility of the plantar aponeurosis, which stretches as the arch is loaded 44 46 .…”
Section: Discussionsupporting
confidence: 90%
“…Recent research, however, challenges this traditional perspective of the windlass mechanism. In a static in vivo loading experiment, Welte et al 14 found that raising the longitudinal arch by dorsiflexing the toes actually decreases the longitudinal arch’s stiffness. In another static in vivo experiment, Farris et al 15 found that the windlass mechanism has little effect on longitudinal arch motion while the arch is experiencing the high loads associated with push-off.…”
Section: Introductionmentioning
confidence: 99%
“…The similarity may arise from the fact that both models include the MTP joint, because hopping requires a considerable MTP joint range of motion, which is captured by the 3MFM and 5MFM. An additional, albeit slightly unrelated consideration, is that the presence of the MTP joint may also better capture intrinsic foot mechanics such as the windlass mechanism, which occurs with dorsiflexion of the MTP joint, increases plantar fascia tension, and transitions the arch from compliant to rigid and generates propulsion . Thus, the MTP joint in 3MFM and 5MFM may better capture the range of motion and perhaps other intrinsic muscle mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, if the patient is standing, the longitudinal medial arch may flatten, but it can also increase with extension of the metacarpophalangeal (MTP) joints. 22 In case of the ICFSG score, cavus deformity is evaluated with the foot dorsiflexed and depending on the appearance of the medial longitudinal arch it can be rated moderate or severe. This method is subjective and might have contributed to the increased rate of cavus deformities reported in this study, particularly if there is some degree of associated extension of the first MTP joint during ankle dorsiflexion.…”
Section: Discussionmentioning
confidence: 99%